2005
DOI: 10.1037/0735-7044.119.6.1477
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anxiety-like behavior in adolescent and adult sprague-dawley rats.

Abstract: The conditions under which age differences in anxiety are observed in rodents are unclear. These studies explored the influence of test condition on anxiety-like behavior in adolescent and adult rats using the light-dark box. Behavior was assessed under different illumination levels (30 or 60 lux) and after brief stress (restraint or bright light). Anxiety-like behavior did not differ in the 30-lux test but was increased in adolescents in the 60-lux test. Restraint increased anxiety-like behavior in adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 39 publications
3
48
0
Order By: Relevance
“…These early adolescent rats were reported to either not differ from adults under low-light conditions (Slawecki, 2005) or were less anxious than adults (Doremus et al, 2004). Adolescents were more anxious than adults after brief restraint stress or when tested under bright light conditions (Slawecki, 2005). Further work is needed to determine more clearly when adolescent animals become fully adult-like in their levels of anxiety.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These early adolescent rats were reported to either not differ from adults under low-light conditions (Slawecki, 2005) or were less anxious than adults (Doremus et al, 2004). Adolescents were more anxious than adults after brief restraint stress or when tested under bright light conditions (Slawecki, 2005). Further work is needed to determine more clearly when adolescent animals become fully adult-like in their levels of anxiety.…”
Section: Discussionmentioning
confidence: 98%
“…These methods are frequently used to test the effectiveness of anxiolytics in adults but are rarely used in young rats. Doremus, Varlinskaya, and Spear (2004) reported that adolescents are less anxious than adults, whereas Slawecki (2005) reported adolescents were not different than adults unless stressed. Remarkably, baseline behavior of preweaning infants has not been characterized using these paradigms.…”
mentioning
confidence: 99%
“…While less research has been conducted in mice, relatively lesser anxiety-like behavior and relatively greater exploration of novel environments has been reported in some but not all studies of adolescent mice [1,2,29,34,48]. Existing data on stress-reactivity in adolescent mice is also somewhat inconsistent, with studies showing both attenuated and exaggerated neuroendocrine, neural and behavioral responses to stress relative to adults [2,10,43,48,53], and to our knowledge little work has been conducted on depression-related behaviors.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies in rodents have shown that adolescents exhibit differences from adult rodents on measures of fear-, anxiety-and depression-related behaviors and reactivity to stress (for recent reviews, see [3,43]). For example, adolescent rats have been found to exhibit either lesser, greater or normal levels of anxiety-like behavior in various behavioral assays as compared to adults [9,13,15,18,25,41,43,51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation